Effects of Curcumin and Nanocurcumin supplementation on serum brain-derived neurotrophic factor and some complications in type 2 diabetic rats - Ali Shamsi Goushki; Zinat Mortazavi; Fatemeh Behrasi; Ali Ebrahimkhani; Razieh Hosseini (Nanomedicine Journal, 2023)
Objective(s): One of the most important neurotrophins is brain-derived neurotrophic factor (BDNF) that is closely associated with insulin resistance and Type 2 Diabetes Mellitus (T2DM). This study was done under the objective of investigating the effects of curcumin (CUR) and nano-curcumin (nCUR) on serum levels of BDNF, fasting blood sugar (FBS), water and food intake, and body weight in T2DM rats. Materials and Methods: Our work required the division of 48 male Wistar rats into the 6 groups of Control, diabetic, diabetic treated with two doses of CUR and nCUR (100 and 200 mg/kg), T2DM induced rats by intraperitoneal injection of Streptozotocin, and nicotinamide in the fasting state. Once the rats received nCUR and CUR doses through gavage for 28 days, their Serum level of BDNF was measured at the end of intervention period, while their body weight, FBS, and food and water intake were also examined at both onset and ending of this period.Results: Considering the effect of curcumin and nano-curcumin administration on the induced significant increase in serum BDNF and decrease in FBS, food, and water intake in T2DM rats (P<0.05), we can confirm the superior effectiveness of nano-curcumin 100 in serum BDNF elevation than curcumin (P<0.05). It is also notable that the body weight of intervention groups did not face any significant reduction when compared to that of diabetic control group.Conclusion: These findings provide evidence for the beneficial effects of CUR and nCUR as an antidiabetic agent, which can be potentially considered as an adjunct for the available diabetes therapies.